LIKUIDITAS SAHAM DAN AKRUAL DALAM KAITANNYA DENGAN KEINFORMATIFAN LABA - Titania Sifera Febriani (Jurnal Riset Manajemen dan Bisnis, 2023)
ABSTRACT The financial statement contains profit information which needed by the market to make decisions, but the expected earnings does not always match with the actual profit. This difference is called unexpected earnings or surprise earnings which will cause a market reaction in the form of changes in stock prices around the date of issuance of financial statements. Changes in stock prices lead to abnormal stock returns. This study examines the effect of stock liquidity and earnings management on earnings information. The sample used are manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. Earnings informativeness is measured using Earnings Response Coefficient (ERC), stock liquidity is measured using bid-ask spread, and earnings management is measured using the Jones Modified model (Dechow, 1995). The results of the first study, stock liquidity have a significant negative effect on earnings informativeness. The results of the second study, discretionary accruals have a significant negative effect on earnings informativeness, while the results of the third study show no influence between non-discretionary accruals and earnings informativeness. Keywords: Earnings Informativeness, Stock Liquidity, Earnings Management, Earnings Response Coefficient ABSTRAK Dalam laporan keuangan terdapat informasi laba yang sangat dibutuhkan pasar untuk membuat keputusan, namun laba yang diharapkan investor tidak selalu sesuai dengan laba sebenarnya atau laba aktual. Perbedaan ini disebut dengan unexpected earnings atau laba kejutan yang akan menyebabkan reaksi pasar berupa perubahan harga saham di sekitar tanggal penerbitan laporan keuangan. Perubahan harga saham menyebabkan adanya abnormal return saham. Penelitian ini menguji pengaruh stock liquidity dan earnings management terhadap earnings informativeness. Sampel yang digunakan adalah perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia dari tahun 2015-2017. Pengukuran earnings informativeness menggunakan Earnings Response Coefficient (ERC), pengukuran stock liquidity menggunakan bid ask spread, dan pengukuran earnings management menggunakan model Modifikasi Jones (Dechow, 1995). Hasil penelitian pertama stock liquidity berpengaruh negatif signifikan terhadap earnings informativeness. Hasil penelitian kedua discretionary accrual berpengaruh negatif signifikan terhadap earnings informativeness, sedangkan hasil penelitian ketiga menunjukkan tidak adanya pengaruh antara non-discretionary accrual dengan earnings informartiveness. Kata kunci: Keinformatifan Laba, Likuiditas Saham, Manajemen Laba, Koefisien Respon Laba